Impact of health differences and longitudinal changes on deceleration driving patterns in older adult drivers. (January 2019) - Howcroft, Jennifer; Knoefel, Frank; Wallace, Bruce; Goubran, Rafik; Porter, Michelle M.; Marshall, Shawn
Highlights: Coefficient of variation can measure deceleration pattern variability. Deceleration pattern variability differs between older drivers based on health status. Better cognitive health was associated with greater deceleration variability. Worse physical health was associated with greater deceleration variability. Longitudinal health changes were associated with coefficient of variation changes. Abstract: Naturalistic in-car driving informatics provides opportunities to identify links between driving behaviours and cognitive and physical health status. The coefficient of variation was used to evaluate deceleration event variability (1) for differences between 171 older adult drivers grouped based on physical and cognitive scores and (2) for changes that aligned with longitudinal health changes in 62 older adult drivers. Differences in older adult physical and cognitive health status were related to deceleration event variability. Greater deceleration event variability was identified in individuals with better cognitive health, with two exceptions. There were also deceleration events subsets where individuals with poorer physical health status exhibited greater variability in deceleration patterns than those with better health status. CoV-measured deceleration event variability did significantly decrease for individuals with longitudinal cognitive health decline and for individuals with longitudinal physical health declines (velocity signal only) for decelerations subsets and CoV increased for individuals with longitudinal physical health decline for acceleration and jerk signals for event deceleration subsets. These findings suggest that worse cognitive health may limit older adult driver's ability to adapt deceleration patterns when needed, resulting in lower CoV-measured variability. However, particularly in situations that require less adaptation to deceleration patterns, worse physical health may induce unnecessary variability during deceleration events. Further investigation is warranted to determine whether differences in variability relate to successful braking collision avoidance behaviours.